The effectiveness of transactional analysis on emotional maturity and communication beliefs - Soltani, Ali; Tamannaeifa, Shima (Psychology of Woman Journal, 2021)
Transactional analysis is one of the theories that has paid much attention to interpersonal relationships, the process of life events, and the mutual reactions of people with each other. It has provided practical solutions for interpersonal issues. Therefore, the present study aimed to determine the effectiveness of transactional analysis on emotional maturity and communication beliefs. The research method was quasi-experimental and pre-test-post-test design with a control group. Among the women who volunteered for marriage and were referred to Golabchi Medical Center and Ravane Aram Clinic in Kashan city in the second half of 2019 for pre-marital counseling, 52 people were selected by the available sampling method. They were randomly placed in the experimental group (26 people) and control group (26 people). In the pre-test phase, women answered the emotional maturity questionnaires of Sink and Bhargava (1984) and the communication beliefs of Eidelson and Epstein (1981). The group therapy sessions for the experimental group were held for eight sessions (2 months), and again, at the end of the sessions, the control and experimental groups completed the questionnaires. The covariance analysis method was used to analyze the data. The results showed that transactional analysis training was practical on emotional stability and irrational communication beliefs of women who volunteered for marriage (p<0.05). According to the research findings, it is suggested to use the teachings of transactional analysis in counseling centers to equip women who volunteer for marriage with appropriate and satisfactory communication skills.